1, 2, 4-Diazaphospholide complexes of yttrium(iii), dysprosium(iii), erbium(iii), and europium(ii, iii): synthesis, X-ray structural characterization, and EPR analysis. Issue 3 (15th December 2015) - Wang, Yongli; Guo, Wenzhen; Liu, Dongling; Yang, Ying; Zheng, Wenjun
Abstract : Heteroleptic, charge-separated heterobimetallic, and polymeric alkali metal ate complexes of 1, 2, 4-diazaphospholide yttrium(iii ), dysprosium(iii ), erbium(iii ), europium(iii ) and europium(ii ) were prepared. Abstract : Several structurally characterized heteroleptic, charge-separated heterobimetallic, and polymeric alkali metal ate complexes of 1, 2, 4-diazaphospholide Y(iii ), Dy(iii ), Er(iii ), Eu(iii ), and Eu(ii ) were prepared via the reaction of MCl3 and K[3, 5-R2 dp] in varied ratios at 200–220 °C (M = Y, Dy, Er, Eu; R = t Bu, Ph).